Potential economic impact from the adoption of Brachiaria hybrids resistant to spittlebugs in livestock systems of Colombia, Mexico and Central America - Rivas Ríos, Libardo; Holmann, Federico J. (2005)
Pasture research led by the International Center for Tropical Agriculture (CIAT) and national institutions during the 80's and 90's, contributed with new Brachiaria species with various characteristics and uses that were incorporated with success in livestock production systems in the lowlands of Latin America. Brachiaria brizantha, Brachiaria dictyoneura, Brachiaria humidicola and Brachiaria ruziziensis are some of the forage materials released by research institutions in the region. Despite its indisputable advantages, the Brachiaria genus presents limitations because of its low tolerance to prolonged droughts and its high susceptibility to spittlebug, a pest that causes considerable economic losses to the livestock industry. Thus, most recent research in CIAT's Brachiaria breeding program has focused on the development of a second generation of Brachiaria grasses: outstanding agronomic characteristics, establishment vigor, good sprout capacity, high biomass production and nutritional quality, good seed production, resistant to Rhizotocnia and to multiple spittlebug species. The results of this effort have conveyed to the recent release of Mulato grass, the first hybrid of the Brachiaria genus obtained by CIAT's genetic improvement program. In the waiting list of the second generation of Brachiaria grasses is hybrid #4624 (CIAT 36087), to be released in 2005, having a similar forage quality as Mulato and with all the attributes defined for the second generation of Brachiaria grasses. Moreover, several other hybrids are in advanced stages of evaluation and close to being released as commercial cultivars. The potential economic impact of the adoption of new Brachiaria hybrids on livestock production systems was evaluated using the Economic Model MODEXC. Two regions were considered in Colombia: the Northern Coast and the Eastern Plains. In Mexico, the tropical region; and in Central America, its six constituent countries. The model estimates the economic benefits attributable to the utilization of the new materials, disaggregating per country, region, ecosystem, production system and large social groups (consumers and producers). It works with two types of parameters: the technical ones that characterize the new technology and its process of dissemination, and the economic ones representing the conditions of market supply and demand of both beef and milk affected by the technical change. The benefits of the new technology (from the year 2007) were calculated for a period of 20 years and the results were expressed in terms of the net present value (NPV) and annuities. The estimates were made using alternatively an economic framework of open and closed economy. In a closed economy, without international trade, the NPV of the technological benefits was estimated at US$4,166 million, of which 54% would be generated by the marketing of beef and the rest by milk. Most of the benefits were concentrated in Mexico, US$2,831 (68%); followed by Colombia, US$960 million (23%), and Central America, US$363 million (9%). In order to have criteria on the extent of the estimated technological benefits, the value of beef and milk yield during 2003 was calculated in the reference countries. The NPV is equivalent to 44% of the value of that year, ranging between 16% in Honduras and 78% in Nicaragua. The results show the importance of the dual purpose livestock production system. In most countries, more than half of the technological benefits was generated in this system: Colombia 70%, Central America 62%, and Mexico 50%. When a country is self-sufficient and the surplus resulting from the technical improvements is marketed domestically, the benefits are transferred to consumers who are favored with the reduction in prices, making possible for them to increase consumption. In the case of a closed economy, consumers would capture 83% of total benefits. Trade liberalization implies a re-distributive process favoring producers. Export purchases increase total demand and restrain the fall of domestic prices. In an open-market economy, the share of benefits to producers would rise to 46%. Research investment is conceived as a primary mechanism to achieve two of the most basic social goals: 1) poverty reduction and improvement in equity, and 2) the promotion of economic growth. Having this premise, in order to establish to what extent this technical change contributes to the fulfillment of these goals, the acquired benefits were estimated for the most vulnerable population groups: a) The two quintiles of poor consumers, representing 40% of total population, and b) the small producers. In both schemes, open or closed economy, both groups receive more than one-fourth of the benefits from technical change, 27% and 31%, respectively. This is equivalent to a NPV ranging between US$1,137 to 1,303 millions. Because the hybrids require better soils or fertilizer inputs to maintain forage biomass productivity and quality, the study was made with conservative hypotheses about changes in productivity and the size of the area to be planted. Despite the definition of the levels of critical variables, especially those associated with the productivity and the adoption of the new Brachiaria hybrids, conservative criteria were considered in order to avoid overestimating the benefits; it is important to evaluate the sensitivity of these, against undesirable changes of those variables. For this purpose, three alternative scenarios were established: 1) The reduction of 50% of the area cultivated with new Brachiaria hybrids, 2) the reduction of 10% in the yields of the new materials, and 3) the increase of 50% in the total time of adoption. The most critical variable in the determination of the amount of benefits is yield (productivity) of the new technology, in terms of beef and milk per hectare. The elasticity of the benefits regarding the yields was estimated at 2.2 for Colombia and 1.8 for Central America and Mexico. This suggests that if the yield declines by 1%, the reduction of the social benefits is more than proportional. The social benefits are less elastic with regard to the area planted with new Brachiaria hybrids or the time of adoption. For example, in Colombia, if the area with improved materials declines by one percentage point, the benefits will diminish at approximately six tenths of one point. In all the proposed alternative scenarios, the investment in the development of these new pastures are economically attractive, despite the adverse circumstances proposed in these scenarios. The technological benefits expressed as an annuity (a fixed annual payment received for a specific number of years) shows that the investment for the development of new forage options is very low, less than US$ 20 million, compared with the annual benefits resulting from the use of these new materials.